APLIKASI SISTEM E-LEARNING DALAM DUNIA PENDIDIKAN - Senny Luckyardi; L. Rahman (Universitas Negeri Padang, 2021)
The purpose of this study is to determine the positive effects of e-learning systems on improving student's understanding of concepts and comparing e-learning with old learning system. Nowadays, the internet is one of the way to find informations easily without reading books and attending classes. The method used in this research is literature study method by obtaining information and data from various sources. The results from this study is that e-learning can improve students' cognitive abilitiesas it is easier to access words, powerpoint, html or PDF in the application. The conclusion is that e-learning can be used as a learning innovation that can help teachers and students using the Software Learning Management System.